Diagnostic problems and emergency cardiac surgery in cut-like penetrating cardiac trauma - Bartoszcze, Artur; J. Rams, Daniel; Filip, Grzegorz; Bartuś, Krzysztof; Kapelak, Bogusław; Litwinowicz, Radosław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2021)
Penetrating cardiothoracic injuries have occurred in large numbers throughout the world from ancient times to the present. A small percentage of them, but the most severe, are penetrating cardiac traumas. Fortunately, in the 21st century, it is possible to treat these types of injuries. Stab wounds are the most common cause of penetrating cardiac trauma, interchangeable with gunshot wounds [1–4]. They are more common in males around the age of 30 (second to fourth decade of life according to the cited study) [1–3]. Ventricular injuries account for approximately 60–70% of all cardiac injuries, with the right ventricle being slightly more commonly affected than the left due to its anatomical location [3, 5]. The standard diagnostic methods include focused assessment sonography for trauma (FAST), cardiac echocardiogram (ECHO), multi-slice scan computed tomography (CT) [2, 3] and chest X-ray (CXR) [5, 6]. Hemodynamic instability indicates immediate surgery, while penetrating trauma should be considered in a stable patient with conservative therapy [3, 5]. The access methods of choice in the management of these patients should be median sternotomy or anterolateral thoracotomy [1, 2, 6], pericardiotomy [5] with possible early pericardiocentesis for evacuation of cardiac tamponade depending on the patient’s condition [3]. Pericardial tamponade and hemothorax were common intraoperative findings in penetrating cardiac trauma [2]. In addition, recognizable signs of life on arrival at the hospital combined with early surgical intervention increase the chances of survival [2, 3]. In the literature review by Pereira et al. [1], the mortality rate due to penetrating cardiac trauma varies from 15% to 40% worldwide but reaches 70% in patients who were not transported to hospital according to Kaljusto et al. [3] or 94% in the study by Campbell et al. [4]. The immediate causes of death in penetrating cardiac trauma may be three basic factors: hemorrhage, cardiac tamponade or interruption of the excitation conduction mechanism [5] and long-term causes of death such as embolism, infarction, thrombosis or sepsis may also occur as complications [1, 5]. Therefore, the management of a patient with penetrating cardiac trauma is difficult and requires immediate clinical diagnosis and treatment, which has been highlighted as “essential” by Furukawa [6].